Helping interventions aimed at students in difficulty in Mathematics : Some tensions in a Cooperative Engineering device - Novembre, Andrea; Broitman, Claudia (Université de Bretagne Occidentale., 2024)
In this paper we share some excerpts from a study on types of helping interventions aimed at students "in difficulty" in Mathematics. We put in dialogue the mathematical learning of students and the didactic activity of teachers based on helping situations. To do so, we developed a Cooperative Engineering through which we designed, implemented, and analysed a didactic unit on a Geometry content for a first year of secondary school. We will focus on certain tensions in the work between researchers and teachers that arose from the interpretation of classroom phenomena.
Keywords: Ciencias sociales::Ciencias de la educación